Reflections on the dimensions of trust and trustworthiness among online consumers - Gefen, David (ACM SIGMIS Database: the DATABASE for Advances in Information Systems, 2002)
Trust is emerging as a potentially central aspect leading to IT acceptance. It is especially needed in the case of gaining and later retaining consumers of online vendors. This has been shown by previous research using single dimensional constructs. But trust can also be viewed as a multi-dimensional construct combining specific beliefs (sometimes labeled as trustworthiness) that either directly or through an overall assessment of trust influence relevant behavioral intentions. To show the need to examine trust in a multi-dimensional perspective, this study proposes a three-dimensional scale of trustworthiness dealing with integrity, benevolence, and ability in the unique case of online consumer trust, and then shows the importance of examining the effects of each dimension individually. The data show that trustworthiness and trust should not be regarded as a single construct with a single effect. Rather, different beliefs influence different consumer activity intentions. Window-shopping intentions was affected by the ability-trustworthiness of the vendor, while overall trust in the vendor and its integrity-trustworthiness affected purchase intentions. The importance of differentiating among online customer activities and what dimensions of trustworthiness affect each is discussed.